Analisis Program Indonesia Pintar dalam Mengurangi Putus Sekolah di Kabupaten Bandung - Randi Purnama; Izzatusholekha Izzatusholekha (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This research is to conduct an analysis of the Smart Indonesia Program (PIP) in reducing school dropouts in Bandung Regency. Using secondary data analysis through observations and literature studies with the focus of this research directed at analyzing program criteria, namely; Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The results showed that in terms of effectiveness it was effective in reducing the dropout rate. In terms of efficiency, there are still students who should receive PIP that have not been touched by the program. In terms of adequacy, it is effective in reducing the dropout rate. In terms of equitable distribution, the program has not been evenly distributed. In terms of responsiveness, the lack of socialization and information obtained by the community and educational institutions is not optimal. In terms of accuracy, the distribution and supervision of the use of program funds have not been precise.